2019
DOI: 10.1002/jor.24210
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of age on implant integration in a rat model: A longitudinal in vivo microct study

Abstract: The effect of age on implant fixation in bone is not always considered during the design of preclinical models. The decision on animal's age is often related to practical or historical reasons, which ultimately may affect the reproducibility of results. This study aimed to quantify the effect of age by monitoring the fixation of contrast‐enhanced PEEK screws in rats, hypothesizing that the kinetics of fixation is impaired in older animals but that age effects are less severe than osteoporotic effects. The time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Consent to perform this study was granted by the ethical committee of the canton of Graubünden in Switzerland (approval number 05/2015) and was carried out in an AAALAC‐accredited research institute. Our previously reported model of ODRI in the rat proximal tibia was used, 20,21 utilizing polyetheretherketone (PEEK) screws. A total of 72 rats were included in the study (overview of grouping shown in Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consent to perform this study was granted by the ethical committee of the canton of Graubünden in Switzerland (approval number 05/2015) and was carried out in an AAALAC‐accredited research institute. Our previously reported model of ODRI in the rat proximal tibia was used, 20,21 utilizing polyetheretherketone (PEEK) screws. A total of 72 rats were included in the study (overview of grouping shown in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Skeletally mature, adult female, specific pathogen‐free Wistar rats, purchased from Charles River at 9–10 weeks of age, were used in this study after a minimum 2‐week acclimatization period. Animal monitoring, care, and potential exclusion criteria were as previously described 20,21 . Animals were randomly allocated to either OVX or non‐OVX groups and subsequent subgroupings of infected/noninfected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to study osseointegration and fixation properties, animal models were established for material evaluation [24]. It has been established that osteoporosis can affect the fixation and osseointegration of implants [25,26], in particular, giving the different responses of osteoporotic cortical and trabecular bone to material implantation [27]. Therefore, establishing the structural features of bone tissue around porous implant materials is important for selecting a particular material for use in patients with low bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…In order to study osseointegration and xation properties animal models were established for material evaluation [24]. It has been established that osteoporosis can affect the xation and osseointegration of implants [25,26], in particular, giving the different response of osteoporotic cortical and trabecular bone to material implantation [27]. Therefore, establishing the structural features of bone tissue around porous implant materials is important for selecting a particular material for use in patients with low bone mineral density.…”
Section: Introductionmentioning
confidence: 99%